Genome‐wide association study reveals the locus responsible for microtia in Valle del Belice sheep breed. (30th August 2018) - Mastrangelo, S.; Sottile, G.; Sutera, A. M.; Di Gerlando, R.; Tolone, M.; Moscarelli, A.; Sardina, M. T.; Portolano, B.
Summary: Microtia is a congenital deformity of the outer ear with phenotypes varying from a small auricle to total absence (anotia). The genetic basis is still poorly understood, and very few studies have been performed in sheep. Valle del Belice sheep is a breed showing microtia. The aim of this study was to identify the potential genomic regions involved in microtia in sheep. A total of 40 individuals, 20 with microtia and 20 normal, were genotyped with the Illumina OvineSNP50 BeadChip. The comparison among the results from a genome‐wide association study, Fisher's exact test and F ST analysis revealed a single strong association signal: rs419889303 on chromosome 1, located within intron 3 of the CLRN1 gene. Our study suggests for the first time that this novel candidate gene is responsible for microtia in sheep. Additional analysis based on the sequencing would help confirm our findings and allow for the proposal of a precise genetic basis for microtia in sheep.